2017
DOI: 10.1038/ajg.2017.53
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Intensive Bowel Cleansing Regimens in Patients With Previous Poor Bowel Preparation: A Randomized Controlled Study

Abstract: After 3-day low-residue diet and oral bisacodyl before colonoscopy, colon cleansing with 4-L split-dose PEG was superior to 2-L split-dose PEG+Asc in patients with previous inadequate cleansing. (EUDRACT: 2013-002506-31, NCT02073552).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 26 publications
1
33
2
Order By: Relevance
“…Nonetheless, it is reported that 1 in 7 patients may not be compliant to bowel preparation regimen mainly due to the volume [19]. Improved results of preparation are achieved with better compliance, which has been shown to be related to decreased bowel preparation volume, palatability and regimen simplicity [2,17,[19][20][21]. We found that 100% of subjects who received low volume preparation nished their bowel preparation completely, in opposition to medium volume preparation (75%) and high volume preparation (77.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is reported that 1 in 7 patients may not be compliant to bowel preparation regimen mainly due to the volume [19]. Improved results of preparation are achieved with better compliance, which has been shown to be related to decreased bowel preparation volume, palatability and regimen simplicity [2,17,[19][20][21]. We found that 100% of subjects who received low volume preparation nished their bowel preparation completely, in opposition to medium volume preparation (75%) and high volume preparation (77.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed better bowel cleansing with 4‐L split‐dose preparation . In comparison with the PEG‐ELS nonsplit regimen regardless of dosage, a PEG‐ELS split‐dose regimen (2‐L on the day before procedure +2‐L on the day of the procedure) causes significantly better bowel cleansing .…”
Section: Discussionmentioning
confidence: 99%
“…While several predictors of poor BP have been reported, effective management strategies to improve BP in patients at high risk are unproven . Stimulant laxatives have shown some benefit when given prior to low‐volume preparations .…”
Section: Introductionmentioning
confidence: 99%